Relasi Kuasa Dalam Kehidupan Single parent (Analisis Wacana Kehidupan Tiga Single parent di Desa Jiwan, Kabupaten Madiun) - Maliki, Mohammad Adam; Arifiyanti, Jati (Jurnal ENTITAS SOSIOLOGI, 2021)
Women who are separated from their partners either by divorce or death will change their status to become single parents. Not a choice, destiny life that makes them have that social status. Problems and pressures will come along with this social status. This study aims to find out how the knowledge of single parents in Jiwan Village. This problem is examined using the theory of power relations from Foucault. This theory is relevant to the issues raised in the study because every single parent will have a relationship that is in accordance with the surrounding environment. This type of research is a qualitative research with the Genaology research method from Foucault. This study uses a purposive method in the selection of informants, and uses the method of observation, interviews, and documentation in data collection. The analysis of this study uses data triangulation and in the data validity test the researcher makes a comparison of field data with other supporting literature. The research results obtained are found in the village of Jiwan Single parent phenomenon with the relationship of support together with support and social support. Ms. Anik has a power relation by becoming the coordinator and alumni of her junior and senior high school treasurers, Ms. Siti Chotidjah has a power relation as the recitation chair, and Ms. Jatmiko has a power relation as the head of social gathering in Jiwan Village. Keywords: Single Parents, Power Relations, Knowledge Wanita yang berpisah dengan pasangannya baik dikarenakan perceraian atau kematian akan berubah statusnya menjadi single parent. Bukan sebuah pilihan, melainkan takdir kehidupan yang membuat mereka memiliki status sosial tersebut. Permasalahan dan tekanan akan datang seiring dengan adanya status sosial tersebut. Penelitian ini bertujuan untuk mengetahui bagaimana wacana pengetahuan relasi kuasa single parent di Desa Jiwan. Isu ini dikaji menggunakan teori relasi kekuasaan dari Foucault. Teori ini relevan dengan isu yang diangkat dalam penelitian karena setiap single parent akan memiliki relasi kuasa atas dirinya dengan lingkungan sekitarnya. Jenis penelitian ini adalah penelitian kualitatif dengan metode pendekatan genaologi dari Foucault. Penelitian ini menggunakan metode purposive dalam pemiliha informan, serta menggunakan metode observasi, wawancara, dan dokumentasi dalam pengumpulan data. Analisis penelitian ini menggunakan triangulasi data serta dalam uji validitas data peneliti melakukan komparasi data lapangan dengan literatur penunjang lainnya. Hasil penelitian yang diperoleh adalah bahwa di Desa Jiwan terdapat fenomena single parent dengan relasi kuasa beserta dengan resistensi dan dukungan sosialnya.Kata Kunci : Single parent, Relasi Kuasa, Pengetahuan